Reading Argumentative Texts: Effects of the Presence-Absence of Connectives in Reading Comprehension and Cognitive Effort - Hector Limón-Fernández; Luis Miguel Sánchez-Loyo; Luis Alfredo Mayoral-Gutiérrez (Revista Costarricense de Psicología)
Recent studies prove a strong association between reading and eye movements. Few investigations report the role of connectors and prior knowledge during reading in Spanish, as well as their association with eye movements. The present study aims to evaluate the effects of the presenceabsence of connectors in two argumentative texts on cognitive effort and reading comprehension. Forty-one psychology undergraduate students participated in a reading comprehension task, while their eye movements were recorded. The condition with connectors was related to prior knowledge, the slide time fixation, the slide number fixations, and the slide return fixations. The condition without connectors was related to the return fixations, the time fixation, and the number of fixations. Prior knowledge was correlated with the total time fixation, the total return fixations, and comprehension. This suggests that during reading without connectors more cognitive effort is required, observed in the return fixations; moreover, prior knowledge has an important role in the visual strategies required to process and obtain a representation of text. But participant performance was still good as observed in the scores of the reading comprehension task.